Pengaruh Financial Knowledge Dan Financial Behavior Terhadap Perilaku Konsumtif - Itsnain Mabrurah; Nur Azizah (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
In the era of globalization, the rapid development of technology affects people's lifestyles, encouraging high consumptive behavior. This phenomenon is especially seen in students, who are often trapped in the purchase of goods not only for needs, but also for desires and social status. This study aims to evaluate the influence of financial knowledge and financial behavior on consumptive behavior among students of the Department of Accounting, University of Islam Malang. The method used was a quantitative approach with an explanatory design, involving 196 students as a sample from a total population of 386 students. Data was collected using a questionnaire and analyzed using the Partial Least Square (PLS) technique. The results showed that financial knowledge had a significant effect on financial behavior and consumptive behavior, while financial behavior also had a significant effect on consumptive behavior. Convergence and discriminatory validity are tested with AVE and cross loading, which indicates all constructs are valid. The reliability test showed that the composite value of reliability and Cronbach's Alpha was more than 0.70. The R-square test shows that consumptive behavior is explained 90% by financial knowledge and financial behavior, while financial behavior is explained by 73.9% by financial knowledge. In conclusion, both financial knowledge and financial behavior have a significant influence on students' consumptive behavior.